3-Dimensional QSAR and molecular docking studies of a series of indole analogues as inhibitors of human non-pancreatic secretory phospholipase A2 - Singh, Kulwinder; ., Monika; Verma, Neelam (International Journal of Research in Medical Sciences, 2017)
Background:Design and development of new drugs is simplified and made more cost-effective because of the advances in the concepts of Quantitative Structure-Activity Relationship (QSAR) studies. A methodology of QSAR studies is one of the approaches to the rational drug design. Methods:3-Dimensional QSAR studies were performed on a series of indole analogues as inhibitors of human non-pancreatic secretory phospholipaseA2 (PLA2) by using Scigress explorer software suite. Docking studies of these compounds were also performed to understand the interactions with amino acid residues of PLA2 protein. Results:The multiple linear regression analysis was used to correlate the physicochemical descriptors with the PLA2 inhibitory activity of 20 training set of compounds and the best QSAR model was developed. The best model was validated using leave-one-out method and found to be statistically significant, with coefficient of determination (r2) of 0.788. This model was further used to predict the PLA2 inhibitory activity of 12 test set of compounds. Docking analysis revealed that most of the compounds formed H-bond interactions with amino acid residues of PLA2 protein (PDB ID: 1DB4). Predicted pIC50 value of one of the test compounds was 7.454 and it showed H-bond interactions with Asp48, Cys44, His27, Gly29 and Gly31 residues. Conclusion:The present study shall help in rational drug design and synthesis of new selective PLA2 inhibitors with predetermined affinity and activity and provides valuable information for the understanding of interactions between PLA2 and the novel indole analogue compounds.